Investigations on New Electrolyte Composition and Modified Membrane for High Voltage Zinc−Manganese Hybrid Redox Flow Batteries. Issue 9 (18th June 2021) - Naresh, Raghu pandiyan; Mariyappan, K.; Dixon, Ditty; Ulaganathan, M.; Ragupathy, P.
Abstract: In this work, the effect of electrolyte composition and the pore filled membrane was investigated in zinc−manganese (Zn−Mn) hybrid redox flow battery (HRFB). Among the studied electrolytes compositions, sulfate‐based electrolyte composition exhibits an improved performance at various conditions. Further, to minimize the ion crossover, the Daramic membrane is modified using polyacrylonitrile (PAN) as a pore filling agent. Hence, the flow cell fabricated with the optimized electrolyte and modified membrane enhanced the overall cell performance, particularly the energy efficiency of 75.45 % was achieved for the optimized conditions. As configured Zn−Mn flow cell system showed high avg. discharge plateau of 1.91 V at 10 mA cm −2 . Further, the cell employed the modified membrane experienced the highly improved performance up to 40 mA cm −2 . Besides that, the durability of the Zn−Mn system employing PAN filled Daramic membrane revealed the consistent cell performance over 100 galvanostatic charge‐discharge (GCD) cycles. Thus, the proposed sulfate‐based precursors electrolyte combinations and PAN filled Daramic membrane can be considered as a proficient candidate for obtaining better performance Zn−Mn flow cell system. Abstract : Let it flow : The effect of electrolyte composition and the pore filled membrane was investigated in Zn−Mn hybrid redox flow battery (HRFB). The Zn−Mn flow cell with sulfate‐based precursor and pore‐filled membrane showed high discharge plateau of 1.91 V at 10 mA cm −2 . Thus, the proposed system is a promising candidate for next‐generation redox flow batteries.